Telehealth Opportunities for the Otolaryngologist: A Silver Lining During the COVID-19 Pandemic. (July 2020) - Shipchandler, Taha Z.; Nesemeier, B. Ryan; Parker, Noah P.; Vernon, Dominic; Campiti, Vincent J.; Anthony, Benjamin P.; Alwani, Mohamedkazim M.; Illing, Elisa A.; Ting, Jonathan Y.
The utilization of telemedicine has seen a relatively slow progression over the past 50 years in the US health care system. Technological challenges limiting the ease of use of robust video platforms have been a major factor. Additionally, the perception by many health care providers that telehealth is reserved for only the rural population or that it provides limited value due to the inability to perform in-depth physical examinations contributes to the slow adoption. The COVID-19 pandemic, with its massive disruption in social interaction by way of "stay at home" orders, is serving as a catalyst for improving telehealth. Large health systems are investing millions of dollars and increasing telehealth visit numbers 100-fold to access patients. The "telehealth movement" is here to stay and will undoubtedly be incorporated into providers' daily lives years after the COVID-19 pandemic. By embracing virtual access to health care, otolaryngologists will be able to influence improvements to these systems and broaden access options for patient care well into the future.